Absence of linkage of Noonan syndrome to the neurofibromatosis type 1 locus. Issue 3 (March 1992) - Sharland, M; Taylor, R; Patton, M A; Jeffery, S
Abstract : Eleven families with Noonan syndrome in either two or three generations have been identified. Following the reports of subjects with features of both Noonan syndrome and neurofibromatosis type 1, these pedigrees have been studied using a number of probes at the neurofibromatosis type 1 locus (17q11). A significantly negative lod score was obtained with the intragenic probe NF1-C2, suggesting that the genes for Noonan syndrome and neurofibromatosis type 1 are not contiguous.